(untitled) (Third Sector Social Economic Review, 2010)
In the 1950s, It has been passed to the multi-party parliamentary regime at Turkey. The Republican People’s Party gave up power to the Democratic Party with 1950 elections. In this study,of economic and political events in democrat party period has been trying to assess of the impact on the Turkey economy. Democrat party which has initiated liberalization process has been interrupted by a military coup in 1960’s. Also, foreign relations and policies in 1950-1970, has increased. Turkey’s participation process to the NATO and the EEC and the EU relations has come to order. In this period, some foreign problems have been trying to solve with the Baghdad Pact and the Balkans Pact.